Influence of the ZrB2 content on the anti-oxidation ability of ZrB2-SiC coatings in aerobic environments with broad temperature range. Issue 2 (February 2020) - Ren, Xuanru; Shi, Huilun; Wang, Wenhao; Chu, Hongao; Chen, Peng; Feng, Peizhong; Guo, Litong; Li, Ziyu
Abstract: ZrB2 -SiC coatings with different ZrB2 contents were prepared by liquid phase sintering. The oxidation processes of coatings were explained according to TG results of ZrB2 -SiC coatings and powders tested from 298 K to 1773 K. Results show that, increasing ZrB2 content made the weight of the samples changed from weight-loss of 10.04% to weight-gain of 0.14%, while the fastest weight-loss regions were narrowed, whose inflection points reduced from 1310℃ to 1050℃. Increasing ZrB2 content made the relative oxygen permeability of the ZrB2 -SiC/SiC coatings reduced from 40%–60% to -10%-5%. Increasing ZrB2 content enhanced high-temperature stability of coatings, making final weight of samples changed from weight-loss of 0.16% to weight-gain of 0.11% after oxidation at 1773 K for 200 h. The peeling and dispersion of Zr-oxides formed Zr-B-Si-O compound glass layer, presenting enhanced stability, dispersion strengthening and pinning effect of Zr-oxides, which were responsible for the excellent anti-oxidation protective effect of coatings in a broad temperature region.